Making a Case for Formal School-Based Oral Health Promotion: Oral Health Knowledge, Attitude and Practices of Pupils in Ibadan, Nigeria (2018)
Providing evidence for institution of school-based oral health promotion programs is paramount in developing countries, due to increasing unmet dental needs impacting on quality of life of children. To evaluate oral health knowledge, attitude and practices (KAP) of pupils in a country lacking formal school oral health promotion. A cross-sectional study was conducted among 1,297 pupils in randomly selected primary schools in one city. Information on oral health KAP were obtained using interviewer-administered questionnaire. Responses to questions were graded, standardized, and data analyzed using SPSS. The mean age was 10.6 (_1.7) years. Mean KAP percentage scores were 18.1 (_5.0)%, 18.3 (_4.9)%, and 17.3 (_12.8)%, respectively. Older age, male gender, and previous dental consultations were significantly associated with higher KAP scores. Those who had been educated informally about oral health had higher mean KAP scores (p¼.013, p<.001, and p<.001, respectively). Previous oral health education and consultation with dentists were significant predictors of higher oral health practice scores. Poor oral health KAP exists among the pupils. Those who had consulted the dentist or had oral health education had better KAP. These findings reinforce the need for formal school-based oral health promotion